Analisis Faktor-Faktor Yang Mempengaruhi Pertumbuhan Ekonomi Di Kabupaten Karanganyar Tahun 1991-2014 - Yulianto, Heri; , Siti Fatimah SE,M.Si (2016)
Economic growth is a problem in the long-term economy and is influenced by various factors. This study was conducted to analyze the effect of the population, local revenue and government expenditure to economic growth in Karanganyar district. In this study using multiple linear regression analysis models of Ordinary Least Square (OLS). For purposes of analysis used secondary data (time series) with the vulnerable period covering 1991 to 2014 GRDP data Karanganyar district, the number of residents, local revenue and government expenditure data. The data obtained from the Central Statistics Agency (BPS) Karanganyar district, department of finance and asset management income areas (DPPKAD) Karanganyar district, sources and other relevant sources. The result of the calculation of data normality test with normal distribution model of Jarque Bera, linearity test results with the model of Ramsey Research shaped linear regression model, classic assumption test results showed that there are no issues multicolinearity, no problem heterokedastisitas, and there is no problem of autocorrelation; T test results showed that the variables were significant positive effect on the GDP is the variable of income, while variable population and government spending no significant effect. F test results showed that the model is in use exist, interpretation R2 shows that the dependent variable can be explained by the independent variables in the model variation of 5%.